Seeding Stress Resilience through Inoculation - Archana Ashokan; Meenalochani Sivasubramanian; Rupshi Mitra (Neural Plasticity)
Stress is a generalized set of physiological and psychological responses observed when an organism is placed under challenging circumstances. The stress response allows organisms to reattain the equilibrium in face of perturbations. Unfortunately, chronic and/or traumatic exposure to stress frequently overwhelms coping ability of an individual. This is manifested as symptoms affecting emotions and cognition in stress-related mental disorders. Thus environmental interventions that promote resilience in face of stress have much clinical relevance. Focus of the bulk of relevant neurobiological research at present remains on negative aspects of health and psychological outcomes of stress exposure. Yet exposure to the stress itself can promote resilience to subsequent stressful episodes later in the life. This is especially true if the prior stress occurs early in life, is mild in its magnitude, and is controllable by the individual. This articulation has been referred to as “stress inoculation,” reminiscent of resilience to the pathology generated through vaccination by attenuated pathogen itself. Using experimental evidence from animal models, this review explores relationship between nature of the “inoculum” stress and subsequent psychological resilience.